2019
DOI: 10.29244/medkon.24.3.278-286
|View full text |Cite
|
Sign up to set email alerts
|

Ethnobotanical Study of Food Plant in Bentong Community from Barru Regency, South Sulawesi-Indonesia

Abstract: The Bentong people lives in the village of Bulo-Bulo, Barru Regency, South Sulawesi. About 50 years ago, the community still lived a nomadic life, but today the community has settled. Knowledge about the use of plants as food ingredients by the people of the Bentong Tribe has not been recorded. This study aims to record and describe the utilization of food plant species of the Bentong tribe. Data collection through informant interviews, observations, and collection of herbarium specimens to be identified. Data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…The sources of food and fruits are divided into four groups: vegetables (e.g., eggplant, mustard greens, prey onions, chayote, cowpea bean, red beans), fruits (e.g., durian, salak, cempedak, langsat), beverages (e.g., palm sugar, tamarillo, passion fruit, coffee), and staple food substitutes (e.g., cassava, sweet potato, taro and breadfruit). Similar findings were reported by Amboupe et al (2019), who found that the Bentong tribe in Baru Regency, South Sulawesi Province, utilized 70 species of plants as food, comprising four species of staple food, 34 species of vegetables, 33 species of fruits; and five species used for beverages.…”
Section: Plant Usage In Kasssupporting
confidence: 87%
“…The sources of food and fruits are divided into four groups: vegetables (e.g., eggplant, mustard greens, prey onions, chayote, cowpea bean, red beans), fruits (e.g., durian, salak, cempedak, langsat), beverages (e.g., palm sugar, tamarillo, passion fruit, coffee), and staple food substitutes (e.g., cassava, sweet potato, taro and breadfruit). Similar findings were reported by Amboupe et al (2019), who found that the Bentong tribe in Baru Regency, South Sulawesi Province, utilized 70 species of plants as food, comprising four species of staple food, 34 species of vegetables, 33 species of fruits; and five species used for beverages.…”
Section: Plant Usage In Kasssupporting
confidence: 87%
“…These cultivated plants are the main species planted because they are easy to grow and can be used in a wide variety of dishes. The leaf of M. uttilissima is the most commonly used one as vegetables in many tribes of Indonesia such as Sasak (Sukenti et al 2016), Bentong (Amboupe et al 2019), Sundanese (Cita 2020), and Saibatin (Wakhidah et al 2020). Batak Karo people cooke them for vegetable soups, daun ubi tumbuk, which is prepared by pounding the leaves and adding spices such as Capsicum annum, Allium cepa, Allium sativum, Solanum lycopersicum, coconut milk, the flower of Etlingera elatior and the fruit of Solanum torvum Sw.…”
Section: Wild Edible Plants and Cultivated Plantsmentioning
confidence: 99%
“…The fruit is sometimes eaten fresh and also processed into jams or sweetmeat (Morton 1987;Ochse 1927;Prabaningrum et al 2018;Siregar 2006;Uji 2007;van Holthoon 1999). The Samawa community of Sumbawa Island and the Bentong community of South Sulawesi consume the fruits (Amboupe et al 2019;Rahayu and Rustiami 2017). The species is often used as a substitute for tamarind by the Javanese (van Holthoon 1999).…”
Section: Local Food Usesmentioning
confidence: 99%